Dynamic Interactions of Urban Land Use Efficiency, Industrial Structure, and Carbon Emissions Intensity in Chinese Cities: A Panel Vector Autoregression (PVAR) Approach - Guihong Yang; Xuxi Wang; Li Peng; Xinyue Zhang (Land)
Climatic and environmental issues have attracted considerable attention worldwide. Clarifying the interactions between urban land use efficiency (ULUE), industrial structure (IS), and carbon emissions intensity (CEI) is of considerable importance in promoting resource–economy–environment coordination. The temporal and spatial characteristics of ULUE, IS, and CEI were analyzed based on panel data from 309 cities in China from 2006 to 2021. A PVAR model was established to analyze the long-term and short-term dynamic and causal relationships among the three variables. ULUE, IS, and CEI showed an upward trend, but significant spatial heterogeneity existed. The three variables had a long-term cointegration relationship. Overall, ULUE had a positive effect on IS, and IS had a promotional effect on ULUE. ULUE and IS had bidirectional inhibitory effects on CEI. This indicates that improving ULUE, upgrading IS, improving energy efficiency, and reducing CEI may be necessary measures to mitigate the environmental impact of human activities. These research results can provide theoretical and policy support for promoting the coordination of resources, the economy, and the environment, and for achieving the promotion of urban high-quality green and sustainable development.